Implikasi TikTok terhadap Motivasi dan Aktualisasi Diri - Dina Mariana Siregar; Nusa Panca Menggala (Pusat Riset dan Inovasi Nasional, 2025)
TikTok has become one of the most popular social media platforms among college students, offering a creative and interactive space that can influence their motivation and self-actualization. This research is motivated by the phenomenon of increasing use of TikTok and its potential as a medium for self-development. This research aims to analyze the implications of TikTok on student motivation and self-actualization, especially in increasing enthusiasm for learning and the ability to express personal potential. This research uses a descriptive qualitative approach with a literature study method. Data was analyzed using thematic analysis to identify key themes related to TikTok use. Research findings show that TikTok has a positive impact in increasing learning motivation through interesting and relevant educational content. In addition, this platform supports student self-actualization by providing space for creative expression, identity development, and productive social interaction. The implications of this research show that TikTok can be optimized as a media to support student learning and self-development if used wisely. It is hoped that the results of this research will provide insight for students, educators and policy makers in using social media effectively to support the growth of the younger generation.